Uji Ketahanan Anggrek Hibrida Phalaenopsis terhadap Penyakit Busuk Lunak yang Disebabkan oleh Dickeya dadantii - Firgiyanto, Refa; Aziz, Sandra Arifin; Sukma, Dewi; Giyanto, dan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTOne of the most popular orchids and cultivated by Indonesia and other countries is Phalaenopsis. The main disease of Phalaenopsis orchids in Indonesia is soft rot caused by bacteria Dickeya dadantii. The purpose of this study was to know the resistanctcy of Phalaenopsis hybrid to soft rot disease. The experiment was conducted at the Bacterial Plant Laboratory, Department of Plant Protection, the Greenhouse of Leuwikopo, Bogor Agricultural University, and the plastic house of Alam Sinar Sari Dramaga, Bogor from June 2014 to February 2015. The experimental design was randomized block design with three replications. Five genotypes of hybrid Phalaenopsis were tested, namely Phal. KHM 205, Phal. KHM 1126, Phal. KHM 1318, Phal. AMP 17, and Phal. KHM 2249. Phal. amabilis, Phal. esmeralda, Phal. amboinensis, and Phal. cornu-cervi were used as controls. The resistance testing was performed by inoculating bacteria D. dadantii on leaves of the orchids. The results showed all Phalaenopsis hybrid showed disease symptoms after inoculation. Phal. KHM 2249 had the lowest number of fallen leaves and the highest number of survive plants compared to the other hybrid Phalaenopsis. Survival rate was likely related to peroxidase activity and leaf thickness.Keywords: fallen leaves, leaf thickness, peroxidase, Phalaenopsis